The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1016/s0920-9964(00)00051-7
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative MR measure of the fornix in schizophrenia

Abstract: Some cognitive disturbances accompanying schizophrenia may be due to abnormalities in the thalamus and components of the limbic system. The fornix is an important white-matter relay pathway connecting these structures and is likely to be affected in schizophrenia as well.Magnetic resonance images of the fornix were analyzed in 15 schizophrenic patients and 15 matched comparison group subjects. Fornix volume was compared between the two groups and was also correlated with the volumes of other neuroanatomical st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…In magnetic resonance imaging (MRI) studies, Zahajszky et al (2001) found no differences in fornix volume between patients with chronic schizophrenia and normal control subjects but did report a significant correlation between fornix and hippocampus volumes only in the schizophrenic group. In contrast, Davies et al (2001) found a significantly larger cross-sectional area of the fornix in early-onset schizophrenia.…”
mentioning
confidence: 96%
“…In magnetic resonance imaging (MRI) studies, Zahajszky et al (2001) found no differences in fornix volume between patients with chronic schizophrenia and normal control subjects but did report a significant correlation between fornix and hippocampus volumes only in the schizophrenic group. In contrast, Davies et al (2001) found a significantly larger cross-sectional area of the fornix in early-onset schizophrenia.…”
mentioning
confidence: 96%
“…MR imaging found no marked changes in fornix volume in schizophrenic patients, but the fornix volume correlated significantly with the volumes of other limbic system structures in schizophrenic patients, but not in controls. 32) On the other hand, the mean cross-sectional fornix area in patients with schizophrenia was significantly larger than in normal subjects. 9) In another study, the fiber number or structure of the fornix was abnormal in schizophrenic patients and men had a lower fiber density in the fornix than in women.…”
Section: Discussionmentioning
confidence: 90%
“…Differences in cell densities between the left and right hippocampi have been described recently in only epileptic male patients, and fornix asymmetry could correspond to hippocampal asymmetry, since the fornix connects the hippocampal formation to the mammillary body. [32][33][34] Significant differences in volume were observed between the right and left sides of the hippocampus, amygdala, fornix, and mammillary bodies in healthy individuals, whereas there was no volume difference between the hemispheres. 5) Asymmetry in the size of the fornix was present in patients with seizures caused by unilateral hippocampal sclerosis and MR imaging showed volume loss of the fornix ipsilateral to the side with hippocampal sclerosis.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Both the gray and white matter components of the limbic system have been studied by using MR imaging in several brain disorders, such as epilepsy (3)(4)(5)(6)(7), dementia (8,9), and schizophrenia (10). Until recently, the study of white matter bundles was restricted to postmortem dissection or section-bysection evaluation by in vivo medical imaging both in terms of the tissue's signal intensity and/or volume measurements.…”
mentioning
confidence: 99%